2004
DOI: 10.1039/b409614b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and stereochemistry of S-bridged CoIIIMCoIII(M = PdII, PtII) trinuclear complexes containing two non-bridging thiolato groups: building blocks for the construction of chiral heterometallic aggregates

Abstract: The reaction of fac(S)-[Co(aet)(3)](aet = aminoethanethiolate) with [PdCl(4)](2-) in a 2:1 ratio in water gave an S-bridged Co(III)Pd(II)Co(III) trinuclear complex composed of two mer(S)-[Co(aet)(3)] units, [Pd[Co(aet)(3)](2)](2+)([1](2+)). In [1](2+), each of the two mer(S)-[Co(aet)(3)] units is bound to a square-planar Pd(II) ion through two of three thiolato groups, leaving two non-bridging thiolato groups at the terminal. Of two geometrical forms, syn and anti, possible for [Pd[Co(aet)(3)](2)](2+), which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…This absorption spectrum coincides well with that of 2 mol of [Pd{Co(aet) 2 (bztea)} 2 ] 4+ (bztea = benzyl-2-thioethylamine), in which two non-bridging S atoms for [Pd{Co(aet) 3 } 2 ] 2+ is bound by benzyl groups [23]. Furthermore, the 13 3 ] octahedra in each Co III Pd II Co III trinuclear unit have the same chiral configuration to give the D 2 or K 2 form, like the parental [Pd{Co(aet) 3 } 2 ] 2+ [22]. Furthermore, the same configurational Co III Pd II Co III trinuclear units are connected by o-xyl 2+ moieties to afford only the D 4 and K 4 isomers.…”
Section: Synthesis and Characterization Of [{Comentioning
confidence: 94%
See 2 more Smart Citations
“…This absorption spectrum coincides well with that of 2 mol of [Pd{Co(aet) 2 (bztea)} 2 ] 4+ (bztea = benzyl-2-thioethylamine), in which two non-bridging S atoms for [Pd{Co(aet) 3 } 2 ] 2+ is bound by benzyl groups [23]. Furthermore, the 13 3 ] octahedra in each Co III Pd II Co III trinuclear unit have the same chiral configuration to give the D 2 or K 2 form, like the parental [Pd{Co(aet) 3 } 2 ] 2+ [22]. Furthermore, the same configurational Co III Pd II Co III trinuclear units are connected by o-xyl 2+ moieties to afford only the D 4 and K 4 isomers.…”
Section: Synthesis and Characterization Of [{Comentioning
confidence: 94%
“…Treatment of a dark brown aqueous solution of [Pd{Co(aet) 3 } 2 ] 2+ , which has two non-bridging thiolato groups at the terminal [22], with o-dibromoxylene (oxylBr 2 ) in a 1:1 ratio gave a dark-red solution. When the reaction solution was chromatographed on an SP-Sephadex C-25 column, only one red-brown band was eluted with a 1.0 mol dm À3 NaCl aqueous solution.…”
Section: Synthesis and Characterization Of [{Comentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction of the syn-isomer with [AuCl{S(CH 2 CH 2 OH) 2 }] led to the formation of an S-bridged octanuclear metallocycle, [Au 2 {Pt[CoL 3 ] 2 } 2 ] 6+ . 225…”
Section: Coordination Chemistrymentioning
confidence: 99%
“…Our continued interest in the stereochemical and electrochemical properties of S-bridged polynuclear complexes composed of fac- ( S )-[M(aet) 3 ] units prompted us to prepare the mononuclear fac- ( S )-[Ru(aet) 3 ] that could be available as the starting complex for the construction of a variety of S-bridged polynuclear structures. In the course of this work, we found that the reactions of Ru III or Ru II with Haet led to the direct isolation of an S-bridged triruthenium complex having two fac- ( S )-[Ru(aet) 3 ] units, [Ru{Ru(aet) 3 } 2 ] 2+ , which is easily oxidized to give the corresponding tricationic species, [Ru{Ru(aet) 3 } 2 ] 3+ .…”
Section: Introductionmentioning
confidence: 99%